Reuse strategies in software engineering - Jaakkola, Hannu (Uporabna informatika (Ljubljana), 2002)
Reuse must be seen within a broad scope in an organization. Independently on the application level, there is always question on the changes in the existing processes, never on the technology itself. We can separate different leveis: the organizational level, process level and practices level. The lowest level - practices - includes generally accepted and adopted ways of working in an organization. The view of reuse is technical and component oriented. The process level specifies the usage of these practices in an organization. In this case the processes are improved to support the reuse approach in different life cycle phases of the product. Higher-level abstractions than single components are the objects of reuse. The highest level in the hierarchy - organizational reuse - builds organizational culture and at the same time integrates processes and practices into daily routines. To be successful a company is expected to be a learning organization. Learning in this context means an ability to accept best practices both from inside and outside the organization. A company needs a reuse infrastructure to apply and process the use of these practices at an organizational level. Reuse is supported by an infrastructure that provides processes of early detection of the reusability (with reuse) and reuse opportunities (for reuse). This paper includes a discussion on the role of reuse in software development organizations. The discussion covers at first general aspects in the topic and the reuse strategy development. Examples of different levels of reuse are introduced.
Keywords: podjetja; ponovna uporaba; računalniški programi; razvoj